Effects of the synthetic estrogen 17α- Ethinylestradiol on aromatase expression, reproductive behavior and sperm quality in the fish Jenynsia multidentata - Roggio, María Angelina (2014)
The synthetic estrogen 17a-ethynylestradiol (EE2) has been increasingly detected in sewage effluents in the last two decades. The aim of the present study was determined if EE2 exposure adversely affected reproduction in internally fertilizing fish species Jenynsia multidentata. Sexual behavior, brain and gonadal aromatase expression as well as sperm quality were evaluated. The brain aromatase expression, reproductive behavior, spermatozoa viability and gonadosomatic index were sensitive biomarkers of EE2 effects on this species. The condition factor, hepatosomatic index, gonadal aromatase expression, sperm count and sperm velocities were unaltered after EE2 exposure. The present work highlights the importance of using a combination of several biomarkers to study the effects of estrogenic compounds, especially when trying to link these results to potential population-level effects.